2020
DOI: 10.3390/plants9091226
|View full text |Cite
|
Sign up to set email alerts
|

Use of Non-Destructive Measurements to Identify Cucurbit Species (Cucurbita maxima and Cucurbita moschata) Tolerant to Waterlogged Conditions

Abstract: Limited information is available regarding the physiology of squash plants grown under waterlogging stress. The objectives of this study were to investigate the growth and physiological performances of three cucurbit species, Cucurbita maxima cultivar (cv.) OK-101 (OK) and Cucurbita moschata cv. Early Price (EP) and Strong Man (SM), in response to waterlogging conditions, and to develop a precise, integrated, and quantitative non-destructive measurement of squash genotypes under stress. All tested plants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Waterlogging induces significant changes in the photosynthetic performance of C3 crops, especially in sensitive plants like cucurbits (He et al, 2018;Barickman et al, 2019;Lin et al, 2020). This response was evident in the current study as A, g s , and E for the two cultivars after 10 DOW treatments were 10.3389/fpls.2022.896244 significantly reduced.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Waterlogging induces significant changes in the photosynthetic performance of C3 crops, especially in sensitive plants like cucurbits (He et al, 2018;Barickman et al, 2019;Lin et al, 2020). This response was evident in the current study as A, g s , and E for the two cultivars after 10 DOW treatments were 10.3389/fpls.2022.896244 significantly reduced.…”
Section: Discussionsupporting
confidence: 60%
“…The substantial decline in the rate of photosynthesis is another characteristic feature of plants subjected to waterlogging conditions. Previous studies have demonstrated the sensitivity of photosynthesis in many crops, including cucumber (Barickman et al, 2019), squash (Lin et al, 2020), tomato (Bhatt et al, 2015), and watermelon (Yetisir et al, 2006). For instance, within the first day of waterlogging treatment, cucumber plants' CO 2 assimilation rate (A) rate declined rapidly (Kang et al, 2009;Barickman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Waterlogging induces significant changes in the photosynthetic performance of C3 crops, especially in sensitive plants like cucurbits (He, Yu, Li, Du & Guo 2018;Barickman et al 2019;Lin et al 2020). This response was evident in the current study as A, g s , and E for the two cultivars after 10 DOW treatments were significantly reduced.…”
Section: Discussionsupporting
confidence: 58%
“…The substantial decline in the rate of photosynthesis is another characteristic feature of plants subjected to waterlogging conditions. Previous studies have demonstrated the sensitivity of photosynthesis in many crops, including cucumber (Barickman, Simpson & Sams 2019), squash (Lin, Lin, Huang & Su 2020), tomato (Bhatt et al 2015), and watermelon (Yetisir, C ¸aliskan, Soylu & Sakar 2006). For instance, within the first day of waterlogging treatment, cucumber plants' CO 2 assimilation rate (A) rate declined rapidly (Kang, Guo, Li & Duan 2009;Barickman et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…
Flooding, a kind of abiotic stress, causes serious harm to plant growth and development by interfering a series of physiological and biochemical activities of plants, finally resulting in the death of the plant. Under flooded conditions, the roots of plants completely soak in the soil of saturated water, inducing low oxygen or the anaerobic environment in the rhizosphere, leaching of mineral elements, and anaerobic respiration, which is not good for the plant growth (Lin et al 2020). Peach is a widely cultivated, deciduous fruit tree in the world.
…”
mentioning
confidence: 99%